Love thy (partisan) neighbor: Brief befriending meditation reduces affective polarization. (September 2022) - Simonsson, Otto; Narayanan, Jayanth; Marks, Joseph
The rising partisan animus between Democrats and Republicans has significant consequences for American society, both political and nonpolitical. The present study used two preregistered randomized controlled designs to investigate whether scalable meditation interventions could reduce affective polarization, relative to baseline scores measured 1 week earlier, in American adults (Study 1: N = 353; Study 2: N = 246) who affiliated with either the Democratic Party or the Republican Party. The results suggest that a brief befriending meditation can reduce affective polarization between Democrats and Republicans by increasing positive feelings relatively more for the political outgroup than the political ingroup.